ABUSE OF ECONOMIC AND POLITICAL POWER IN ELECTORAL CAMPAIGNS - Silva, Heloisa Bittencourt Arins; Alencar, Hugo David de Sá; Rodrigues, Jhomerson Souza; Sobrinho, Nathália Murielly Oliveira; Santos, Tiago Cunha dos; Valle, Luciano (CIPEEX, 2025)
This study analyzes the impacts of economic and political abuse of power in Brazilian electoral campaigns, emphasizing its relationship with democratic legitimacy and equal opportunities among candidates. Adopting a qualitative and bibliographic approach, it examines constitutional provisions, especially Article 14 of the 1988 Federal Constitution, the Complementary Law No. 64/1990, the Electoral Code, as well as empirical studies and emblematic cases judged by the Electoral Court. The research demonstrates that, although legal instruments such as the Judicial Electoral Investigation Action (AIJE) and the Action for Annulment of Electoral Mandate (AIME) exist to curb illicit practices, their effectiveness remains limited due to procedural slowness, probative difficulties, and political influences on judicial decisions. The results reveal recurring practices of economic abuse, such as illicit donations, excessive campaign spending, and vote buying, in addition to political abuse, including the manipulative use of social programs, undue pressure on public servants, and promotional use of public resources during election periods. Empirical evidence, such as Silva’s (2018) study, confirms that increased campaign spending is directly correlated with the probability of being accused of abuse, particularly among incumbents. Notable cases, such as the Lava Jato Operation, the electoral actions that led to the ineligibility of former President Jair Bolsonaro, and regional episodes like the annulment of Governor Simão Jatene’s mandate in Pará, illustrate the structural dimension of the problem in Brazil. The study concludes that combating electoral abuse requires not only judicial rigor but also institutional reforms, stronger inspection mechanisms, and greater political awareness by society. Strengthening democracy in Brazil depends on continuous, technical, and impartial efforts to ensure electoral processes truly reflect the sovereign will of the people.